Pendidikan dan Promosi Kesehatan tentang Masalah Hipertensi dan Pola Hidup Bersih Sehat Pada Masyarakat Khususnya Wanita Usia Subur - Dunggio, Abdul Rivai Saleh; Musdalifah, Musdalifah; Peluw, Zulfikar; Rasyid, Djusmadi; Pratiwi, Cici (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Various drug-related problems can be caused by the community's lack of understanding about the use and proper handling of drugs. Providing education on how to use special drugs such as ear drops is very important because there are critical points in ear drops, especially in the method of instillation. Providing incomplete and unclear information on how to use drugs will result in less than optimal therapy so that the drug will not achieve the desired therapeutic effect. This community service activity aims to increase public knowledge about how to use ear drops properly. This service is carried out by providing information through leaflets and explaining directly to the community. Providing education on how to administer ear drops to the community received a good response because most people do not know how to use them properly. The presence of 36 participants and the participants who attended were very enthusiastic in listening to the explanation and actively asked questions related to the use of ear drops and their handling. This can support the realization of government programs in improving health services for the community. This counseling received significant results. Therefore, the PkM TEAM hopes that with this counseling, it can share information about the correct use and handling of ear drops with their family members.